Improvising Policy Governance in Welfare Development: Case Study of Smart City in Madiun City, Indonesia - Aripin, Sofjan; Pratama Putra Salmon, Indra; Yuliani, Isnaeni (Iapa Proceedings Conference, 2024)
A smart city is a comprehensive urban planning model that seeks to address challenges from multiple perspectives and mitigate risks to the well-being of the community. It is evident that the concept of welfare has implications for the happiness of the community. A happy community is an indicator of the success of the local government in achieving its development goals. The concept of happiness is not solely contingent upon material success; rather, it is also dependent upon the interpretation of the process and outcomes of development as beneficial for all stakeholders, including the state, government, society, and external policy makers. This study employs a qualitative method with a case study approach. The findings of this study indicate that the practice of a smart city has been implemented in various forms and has had an impact on the community in Madiun City. This progress is evidenced by advancements in a multitude of development sectors, including social, economic, environmental, technological, and other forms of development. The findings of this study indicate that the government of Madiun City has successfully implemented a smart city initiative, resulting in a range of positive impacts on the community. It is important to note, however, that strengthening leadership and governance is a crucial step, given the reality that changes in leadership often result in shifts in policy direction. Furthermore, establishing a comprehensive legal framework to oversee the smart city program is essential, given that, currently, only a mayor's regulation exists in Madiun City, serving as the sole basis for policy.